2014
DOI: 10.1073/pnas.1408589111
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary tipping points in the capacity to adapt to environmental change

Abstract: In an era of rapid climate change, there is a pressing need to understand how organisms will cope with faster and less predictable variation in environmental conditions. Here we develop a unifying model that predicts evolutionary responses to environmentally driven fluctuating selection and use this theoretical framework to explore the potential consequences of altered environmental cycles. We first show that the parameter space determined by different combinations of predictability and timescale of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
551
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(572 citation statements)
references
References 36 publications
21
551
0
Order By: Relevance
“…Recent research shows clearly that evolutionary processes affect ecological dynamics even over the course of a single generation (30)(31)(32). Our results for the effect of immigration on the dynamics of small populations support these findings and their application to rescuing vulnerable populations from extinction.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research shows clearly that evolutionary processes affect ecological dynamics even over the course of a single generation (30)(31)(32). Our results for the effect of immigration on the dynamics of small populations support these findings and their application to rescuing vulnerable populations from extinction.…”
Section: Discussionsupporting
confidence: 84%
“…The ability to acclimatize to changing thermal conditions is expected to be a primary factor that dictates the vulnerability of taxa to rising temperatures [4][5][6]10,20]. Our broad-scale analysis of thermal tolerance plasticity across ectotherms has many implications for our understanding of the interactions between plasticity and warming.…”
Section: Implications For Climate Changementioning
confidence: 99%
“…As a result, organisms across the globe will be more likely to experience temperatures beyond their physiological limits unless they can in some way buffer themselves from environmental change [2,3]. One mechanism that could greatly reduce the risk of overheating is physiological plasticity in thermal tolerance, such as the reversible changes in thermal tolerance known as acclimation (if measured in the laboratory) or acclimatization (if measured in the field) [4][5][6][7]. For example, the upper thermal tolerance limits of many organisms increase (within individuals) as mean body temperatures rise, meaning that physiological adjustments can potentially compensate for the negative consequences of rising habitat temperatures [8].…”
Section: Introductionmentioning
confidence: 99%
“…This view is now firmly established in the field of 'evo-devo' [6,7], where the interplay between (developmental) mechanisms and evolution is at centre stage. Similarly, studies on gene-regulatory networks [8][9][10] have revealed that network topology strongly affects both the robustness and evolvability of living systems, while recent 'integrative' models [11][12][13] reveal that the mechanisms underlying phenotypic responses can be important for a full understanding of eco-evolutionary processes.…”
Section: Introductionmentioning
confidence: 99%